Antitumor and antimetastatic activities of pectic polysaccharides isolated from persimmon leaves mediated by enhanced natural killer cell activity. (October 2017) - Park, Hye-Ryung; Hwang, Dahyun; Hong, Hee-Do; Shin, Kwang-Soon
Highlights: Three persimmon leaf polysaccharides were prepared by size exclusion chromatography. PLE-II increased the levels of IL-6 and IL-12 from peritoneal macrophages. PLE-II showed antitumor and antimetastatic activities in mice. PLE-0 induced NK cell-mediated antitumor and antimetastatic activities in mice. Abstract: To investigate the antitumor and antimetastatic activities of pectic polysaccharides isolated from persimmon leaves, three polysaccharides (PLE-0, -I, and -II) were prepared. Based on IL-6 cytokine production, PLE-II was selected for further analysis. PLE-II significantly increased IL-6 and IL-12 production in peritoneal macrophages. Moreover, the antitumor and antimetastatic activities of PLE-II were mediated by the activation of natural killer (NK) cells. Depletion of NK cells abolished its antimetastasis activity, thus confirming the role of NK cells in mediating the antimetastatic effect. To determine the commercial potential of PLE, the crude polysaccharide, PLE-0, was administered orally to mice, and its antitumor and antimetastatic activities were evaluated. PLE-0 also induced NK cell-mediated tumoricidal activity and inhibited tumor metastasis in mice in a dose-dependent manner. These data suggest that both PLE-0 and PLE-II have antitumor and antimetastatic activities, and PLE-0 could potentially be used in functional foods and nutraceuticals for cancer prevention.